2007
DOI: 10.1016/j.vetmic.2007.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcription of the major antigenic protein 1 multigene family of Ehrlichia ruminantium in Amblyomma variegatum ticks

Abstract: The rickettsial pathogen Ehrlichia ruminantium causes heartwater in ruminants and is transmitted by ticks of the genus Amblyomma. The map1 gene, encoding the major surface protein MAP1, is a member of a multigene family containing 16 paralogs. In order to investigate differential transcription of genes of the map1 multigene family in vivo in unfed and feeding ticks, RNA was extracted from midguts and salivary glands of E. ruminantium-infected adult female Amblyomma variegatum ticks and analysed by RT-PCR using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
3
16
1
Order By: Relevance
“…This correlated with the amount of parasites that were found in cell culture (10 9 copies/ml) using the map1 real-time PCR (Peixoto et al, 2005). Postigo et al (2007) reported quantification of E. ruminantium in the midgut and salivary glands in ticks (10 6 bacteria per tick) by real-time PCR using the map1 multigene family. The real-time PCR could only detect E. ruminantium parasites in the blood of infected animals at the febrile stage of infection.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This correlated with the amount of parasites that were found in cell culture (10 9 copies/ml) using the map1 real-time PCR (Peixoto et al, 2005). Postigo et al (2007) reported quantification of E. ruminantium in the midgut and salivary glands in ticks (10 6 bacteria per tick) by real-time PCR using the map1 multigene family. The real-time PCR could only detect E. ruminantium parasites in the blood of infected animals at the febrile stage of infection.…”
Section: Discussionmentioning
confidence: 88%
“…E. ruminantium, quantitative real-time PCR was first used to detect the map1 gene in order to monitor cell culture vaccine production (Peixoto et al, 2005). Similarly, Postigo et al (2007) quantified E. ruminantium DNA in ticks and in infected endothelial cell cultures using the map1-1 gene. However, both the map1 and map1-1 genes are known to be polymorphic ) and therefore may not always be effective for detecting heartwater isolates in the field.…”
Section: Introductionmentioning
confidence: 99%
“…In E. ruminantium, the immunodominant major surface protein expressed in the mammalian host, MAP1, is encoded by a member of a multigene family comprising 16 paralogs (van Heerden et al, 2004) which are differentially transcribed in vitro in endothelial and tick cell cultures (van Heerden et al, 2004;Bekker et al, 2005) and in vivo in tick midguts and salivary glands (Postigo et al, 2007). It is important to determine which proteins from the E. ruminantium map1 cluster, other than MAP1 which is located on the surface of mammalian-stage elementary bodies , are actually expressed and if they are differentially expressed in tick and mammalian cell environments.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations that occur in the surface-exposed proteome upon the transition between host species are less well defined in Anaplasma and Ehrlichia spp., and investigations have been confined to a single protein family, pfam01617. However, comparison of expression of specific outer membrane proteins within this protein family has revealed host cell-dependent switching and shifts in levels of expression of these closely related proteins (6,27,31).…”
mentioning
confidence: 99%